Excellent Corrosion Resistance of Dual‐Phase Bimodal Stainless Steel. Issue 5 (15th February 2019) - Saini, Jaskaran; Arora, Harpreet S.; Grewal, Harpreet S.; Perumal, Gopinath; Ayyagari, Aditya; Salloom, Riyadh; Mukherjee, Sundeep
Abstract : Bimodal microstructures in metals are attractive because they help in achieving high strength and good ductility simultaneously thereby circumventing the strength‐ductility paradox. However, there are few reports and limited understanding of the surface degradation behavior of bimodal alloys. Here, the authors report on the exceptional corrosion resistance of bimodal stainless steel developed using a simple single‐step processing route. The microstructure of bimodal steel comprises of fine martensite (≈200–400 nm) in a matrix of coarse austenitic grains (≈10 μm). The bimodal steel shows significantly lower corrosion rate of 0.001 mm/year in 3.5 wt% NaCl solution compared to 0.088 mm/year for commercially available SS316L stainless steel. The exceptional corrosion behavior of bimodal steel is attributed to favorable electronic properties of its passive layer. Formation of a depletion zone in the passive layer and higher chromium fraction limits the charge transport across metal‐oxide‐solution interface. The current microstructural design strategy is potentially transformative for developing high‐performance structural materials with superior corrosion resistance. Abstract : Development of bimodal and ultra‐fine grain structure in stainless steel . Localized rotation of tool in submerged cooling condition results in dual‐phase bimodal grain structure while transverse motion of the rotating tool results in ultra‐fine grain structure. The dual‐phase bimodal steel shows exceptional corrosion resistance and better mechanical properties compared to ultra‐fine and as‐received steel.